A dual-templating strategy for the scale-up synthesis of dendritic mesoporous silica nanospheres. Issue 23 (15th November 2017) - Liu, Peng-Cheng; Yu, Ye-Jun; Peng, Bo; Ma, Shi-Yu; Ning, Tian-Yu; Shan, Bing-Qian; Yang, Tai-Qun; Xue, Qing-Song; Zhang, Kun; Wu, Peng
Abstract : Mesoporous silica nanoparticles with varied morphologies and pore structures were synthesized on the kilogram scale using cetyltrimethylammonium bromide and an anionic surfactant as co-templates. Abstract : We have demonstrated a facile and green way to synthesize dendritic mesoporous silica nanoparticles (DMSNs) on an ultra-large scale (kg) with cetyltrimethylammonium bromide (CTAB) and an anionic surfactant as dual templates free of organic solvents. In contrast to its co-template role in tuning the packing parameter of the surfactant molecule organization, the anionic surfactant herein acts as a more strongly competitive counterion against the adsorption of negatively charged silicate oligomers (I − ) on the micelles. Based on the new understanding of the interaction between the cationic–anionic surfactant ionic pairs and the silicate oligomers, we proposed a dual template synergistically controlled micelle self-aggregated model to understand the formation mechanism of dendritic MSNs where the anionic surfactant stabilized micelles or micelle blocks are basic self-assembling building units for the formation of center-radial pore channel networks. By using one-pot in situ isomorphous substitution, the metal Ti atom can be easily incorporated into the silica frameworks of DMSNs, and the obtained Ti-DMSN catalyst shows a superior catalytic performance in the epoxidation of cyclohexene over the typical mesoporous Ti-MCM-41 silicas.